The impact of flood on water quality and benthic invertebrate in rivers at Gua Musang, Kelantan - Shamsudin Mustafa Sheikh Dawood, 1992-, author; Salmiati Muhd. Yunus, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2016